Marine spatial planning in Cyprus - Hadjimitsis, Diofantos G.; Agapiou, Athos; Mettas, Christodoulos; Themistocleous, Kyriacos; Evagorou, Evagoras G.; Cuca, Branka; Papoutsa, Christiana; Nisantzi, Argyro; Mamouri, Rodanthi-Elisavet; Soulis, George; Xagoraris, Zafiris; Lysandrou, Vasiliki; et al. (My University, 2015)
Marine Spatial Planning (MSP), which is in concept similar to land-use planning, is a public process by which the relevant Member State's authorities analyse and organise human activities in marine areas to achieve ecological, economic and social objectives. MSP aims to promote sustainable growth of maritime economies, sustainable development of marine areas and sustainable use of marine resources. This paper highlights the importance of MSP and provides basic outcomes of the main European marine development. The already successful MSP plans can provide useful feedback and guidelines for other countries that are in the process of implementation of an integrated MSP, such as Cyprus. This paper presents part of the MSP project, of which 80% funded by the European Regional Development Fund (ERDF) and 20% from national contribution. An overview of the project is presented, including data acquisition, methodology and preliminary results for the implementation of MSP in Cyprus.
Keywords: Activities; Coastal zone management; Mapping; Marine spatial planning